Study on Preparation of Coal Gangue-Based Geopolymer Concrete and Mechanical Properties. (24th June 2021) - Zhang, Daming; Sun, Fangjin; Liu, Tiantian
Abstract : Alkaline dry powder activator, coal gangue, fly ash, and other raw materials are utilized to prepare coal gangue-based geopolymer concrete. The procedures of making the coal gangue-based geopolymer concrete are illustrated firstly. Also, basic mechanical properties, such as compressive strength and flexural strength of the geopolymer concrete, are studied through mechanical tests. The basic mechanical properties of ordinary concrete and coal gangue-based geopolymer concrete with different activation methods were compared and analyzed. Effects of curing temperature, curing time, water-binder ratio, and sand ratio on the basic mechanical properties of coal gangue-based geopolymer concrete activated by alkaline dry powder were studied. The optimal curing temperature, water-binder ratio, and sand ratio range of coal gangue-based geopolymer concrete activated by alkaline dry powder are obtained, respectively.